Ks. Wincenty Myszor jako inicjator i współtwórca wydawnictw informacyjnych z treściami patrystycznymi - Tałuć, Katarzyna; Gołda, Agnieszka (Vox Patrum, 2024)
Among the various forms of scientific texts, lexicographic and encyclopedic studies as well as the entries and articles published in them deserve attention. They are created by researchers with extensive scientific experience. They contribute to general and special encyclopedias, terminological and linguistic dictionaries, including translation dictionaries, lexicons, etc. Patrists also have achievements in the field of information publications. An example is Fr. Wincenty Myszor, for years associated with the Academy of Catholic Theology in Warsaw and the Faculty of Theology of the University of Silesia in Katowice. During his scientific career, he initiated or co-created seventeen encyclopedias, dictionaries and lexicons. Based on the analysis of sources and materials stored in the Archdiocesan Archives in Katowice, the work of the patrolologist was characterized, who from the 1970s to the 21st century cooperated with outstanding representatives of Polish and German patrology, coptology, classical philology, theology and philosophy. He left entries and articles on issues close to his research interests in the publications they edited. He also became known as the author and co-author of translation dictionaries of the Coptic language that are still used today. This type of achievements prove the rank of a scientist who, through this type of activity, provides lasting evidence of knowledge and research competence.